A hydrogen-substituted graphyne nanopowder material and its preparation method and application
By preparing hydrogen-substituted graphyne nanopowder materials, the problem of low adsorption capacity of existing carbon-based adsorbents in heavy metal lead ion adsorption is solved, and efficient lead ion adsorption and good cycle stability are achieved.
Patent Information
- Application Number
- CN202210648217.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-06-09
AI Technical Summary
Existing carbon-based adsorbents face the problems of low adsorption capacity and the need for further physicochemical modification in the adsorption of heavy metal lead ions, which limits their large-scale use in industry.
By preparing hydrogen-substituted graphiteyne nanopowder materials, using triethynylbenzene as the precursor, polymerization reaction is carried out under specific conditions to generate nanopowder materials with high specific surface area and unique pore structure. This material is used as a heavy metal adsorbent directly for the removal of lead ions in aqueous media.
The maximum adsorption amount of lead ions reached 2390mg·g-1, and the adsorption amount did not decrease significantly in 6 cycles, showing good reusability.
Smart Images

Figure CN115888640B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano-adsorption materials, and in particular relates to a hydrogen-substituted graphyne nano-powder material and a preparation method and application thereof. Background Art
[0002] Lead (Pb) is still the most common heavy metal pollutant in the world that harms the environment and human health. Due to its non-degradability and gradual bioaccumulation in organisms, it is considered a risk factor for hypertension, heart disease, stroke and chronic kidney disease. At present, the methods for treating heavy metal lead ions mainly include chemical precipitation, electrolysis, membrane separation, oxidation-reduction, ion exchange, adsorption and the like. Among them, adsorption is one of the main ways to treat heavy metals in water media. For example, CN107362772A discloses a method for preparing biochar for removing heavy metal lead from water bodies. The method uses readily available bamboo as a raw material, and a carbon material with an adsorption capacity of 65.4 mg / g for heavy metals in a water environment is prepared through pyrolysis. For example, CN111013535A discloses a method for preparing a lead adsorbent. First, Fe 3 O 4 Loaded onto graphene oxide to obtain magnetic graphene oxide; then basic calcium phosphate is loaded onto magnetic graphene oxide to finally obtain a lead-adsorbed magnetic graphene oxide composite material. The composite material exhibits an adsorption capacity of 232.8 mg / g. For example, CN108993446A discloses a material preparation of polydopamine-modified carbon nanotubes and is used to quickly remove heavy metal lead ions from wastewater. The maximum saturated adsorption capacity of the adsorbent for lead ions is 98.4 mg / g. It is understood from the above reports that carbon-based materials are widely used in the field of heavy metal lead ion adsorption, and have the advantages of simple operation, strong modifiability, low cost and renewability. However, most carbon-based adsorbents are faced with low adsorption capacity, the need for further physical and chemical modification, etc., which are limited to large-scale use in industry. Therefore, the development of a carbon-based adsorbent with a high adsorption capacity is of great significance for fields such as protecting the environment and maintaining human health.
[0003] Graphdiyne is a planar network structure of all-carbon materials formed by conjugating benzene rings with 1,3-diethyne bonds. The unique acetylene bonds and triangular pore structure of Graphdiyne can not only restrict metal atoms, but also the electron-rich structure of carbon-carbon triple bonds has a strong interaction with metal atoms. These characteristics make Graphdiyne have good lead ion removal performance. For example, Graphdiyne was first reported to be used as an adsorbent to remove lead ions from aqueous solution, with a maximum adsorption capacity of 430 mg / g, showing excellent lead ion removal performance (Liu R, Zhou J, Gao X, et al. Graphdiyne Filter for Decontaminating Lead-Ion-Polluted Water [J]. Advanced Electronic Materials, 2017: 1700122.). However, the most stable ABC three-layer stacking and smaller triangular pore structure of Graphdiyne severely restrict the diffusion and transmission of lead ions between layers, making it show a low adsorption capacity, resulting in many obstacles in the adsorption of heavy metals.
[0004] Reference: He J, Wang N, Cui Z, et al. Hydrogen substituted graphdiyne as carbon-rich flexible electrode for lithium and sodium ion batteries[J]. Nature Communications, 2017, 8(1): 1172. For the first time, hydrogen substituted graphdiyne thin film materials were prepared as independent flexible electrodes for lithium ion and sodium ion batteries, showing 1050 mAh·g -1 and 650mAh g -1 The reversible capacity of hydrogen-substituted graphyne is an extended π-conjugated carbon material composed of diacetylene bonds and benzene rings, and the pore diameter of graphyne is In comparison, the pore size of hydrogen-substituted Graphdyne is enlarged to Hydrogen-substituted graphyne material provides a favorable environment for the rapid diffusion of metal ions inside it. Due to the unique structure of hydrogen-substituted graphyne, it provides a favorable environment for the rapid diffusion of metal ions inside it. It has been studied intensively in the fields of energy storage, solar cells, etc. However, the film structure obtained by the current preparation method severely limits its application in the field of adsorption, especially as an adsorbent for the removal of lead ions in water media, but there is no report. Therefore, it is desired in the art to obtain a hydrogen-substituted graphyne nanomaterial with good dispersibility in liquid media, strong lead ion removal ability, and the ability to purify water resources. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a hydrogen-substituted graphyne nanopowder material and a preparation method and application thereof, and solve the technical problem of low lead ion adsorption in the prior art.
[0006] In order to achieve the above technical purpose, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a hydrogen-substituted graphyne nanopowder material, comprising the following steps: adding a triethynylbenzene solution to a mixture A containing copper foil, reacting at 90 to 110° C. to generate a solid powder, and washing and calcining the solid powder to obtain a hydrogen-substituted graphyne nanopowder material.
[0008] Furthermore, the concentration of the triethynylbenzene solution is 1-3 mg / mL; and the solvent of the triethynylbenzene solution is pyridine.
[0009] Furthermore, the preparation of triethynylbenzene includes the following steps: adding tetrabutylammonium fluoride solution to 1,3,5-tri[(trimethylsilyl)ethynyl]benzene solution, wherein the ratio between 1,3,5-tri[(trimethylsilyl)ethynyl]benzene and tetrabutylammonium fluoride is 200 mg:(1.5-1.8) mmol; stirring the reaction at 2-10° C. for 15-45 minutes under light-proof conditions, and then post-treating to obtain triethynylbenzene.
[0010] Furthermore, the solvents of the 1,3,5-tris[(trimethylsilyl)ethynyl]benzene solution and the tetrabutylammonium fluoride solution are both tetrahydrofuran; and the post-treatment includes dichloromethane extraction, water washing, drying, filtering and evaporating the solvent.
[0011] Furthermore, the mixture A containing copper foil is obtained by placing copper foil in pyridine and preheating at 80-100° C. for 20-40 minutes.
[0012] Furthermore, the reaction is carried out under light-proof conditions, and the reaction time is 5 to 7 days.
[0013] Furthermore, washing is performed by washing with an organic solvent, an acid solution, and an alkali solution.
[0014] Furthermore, the calcination is carried out at 200-400° C. for 2-6 hours.
[0015] In a second aspect, the present invention provides a hydrogen-substituted graphyne nanopowder material obtained by the above preparation method.
[0016] In a third aspect, the present invention provides an application of a hydrogen-substituted graphyne nanopowder material in the adsorption of heavy metals.
[0017] Compared with the prior art, the beneficial effects of the present invention include:
[0018] (1) In the present invention, by controlling the reaction conditions such as reaction temperature, the prepared hydrogen-substituted graphyne material is a nano-powder material. It not only has a large conjugated π bond, an ultra-large pore structure and a diacetylene bond structure with high activity for adsorbing metal ions, but also has a sufficient contact area with the liquid medium in the nano-powder morphology, and can effectively capture heavy metals in the water medium. The special pore structure can improve the diffusion of ions and thus increase the adsorption of heavy metals, and can be used as an adsorbent for heavy metals.
[0019] (2) In the present invention, as a heavy metal adsorbent, the hydrogen-substituted graphyne nanopowder material is the material with the largest lead ion adsorption capacity among the currently reported adsorbent materials. When the material of the present invention is used as a heavy metal adsorbent to remove lead ions in a water medium, the maximum adsorption capacity of lead ions is obtained by fitting the Langmuir isotherm adsorption model to be 2390 mg·g -1 ; and it can be recycled, and the adsorption capacity of the material has not decreased significantly during 6 cycles.
[0020] The present invention applies hydrogen-substituted graphyne nanopowder materials to heavy metal removal for the first time, providing a new opportunity for developing new heavy metal adsorbents and expanding the application of graphyne-based materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure is a reaction pathway diagram for the synthesis of hydrogen-substituted graphyne of the present invention.
[0022] Figure 2 This is a scanning electron microscope image (SEM) of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0023] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0024] Figure 4 This is the X-ray diffraction pattern (XRD) of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0025] Figure 5 This is a Raman spectrum of the hydrogen-substituted graphyne powder material prepared in the embodiment of the present invention.
[0026] Figure 6 This is an X-ray photoelectron spectrum (XPS) of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0027] Figure 7 This is the nitrogen adsorption-desorption isotherm of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0028] Figure 8 This is a curve showing the change in the adsorption amount of a certain concentration of lead ions by the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention over time.
[0029] Fig. 9 Langmuir isotherm adsorption curve of lead ions on the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0030] Fig.10 This is a graph showing the lead ion cyclic adsorption performance of the hydrogen-substituted graphyne powder material prepared in an embodiment of the present invention.
[0031] Fig.11 This is a SEM image of a sample prepared in a comparative example of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0033] The method for preparing the hydrogen-substituted graphyne nanopowder material of the present invention comprises the following steps:
[0034] As a preferred embodiment of the present invention, the hydrogen-substituted graphyne nanopowder material is a hydrogen-substituted graphyne nanopowder material polymerized from triethynylbenzene as a precursor.
[0035] As another preferred embodiment of the present invention, the hydrogen-substituted graphyne nanopowder material polymerized from triethynylbenzene as a precursor is prepared by a chemical method of in-situ cross-coupling reaction.
[0036] For further information, see Figure 1 The chemical method of the in situ cross-coupling reaction comprises the following steps in sequence:
[0037] a. Preparation of the pyridine solution of the precursor triethynylbenzene: First, add tetrabutylammonium fluoride (TBAF) to the tetrahydrofuran (THF) solution of 1,3,5-tri[(trimethylsilyl)ethynyl]benzene and stir at a certain temperature. After the reaction, the solution is extracted with dichloromethane, washed with distilled water, dried with anhydrous sodium sulfate, filtered and the solvent is rotary evaporated to obtain 1,3,5-triethynylbenzene. Add pyridine to obtain a pyridine solution of triethynylbenzene. The reaction system is completed under light-proof conditions; the concentration of the pyridine solution of triethynylbenzene is 1-3 mg / mL.
[0038] b. Pre-treating the copper foil in a pyridine solution under certain conditions to obtain a mixture A; specifically, the mixture A is a mixture in which the copper foil is immersed in pyridine and preheated at 80-100° C. for 20-40 minutes.
[0039] c. Mix the pyridine solution of triethynylbenzene obtained in step a dropwise with the mixture A obtained in step b, and obtain a yellow-brown solid powder under certain reaction conditions. Specifically, the reaction system should be completed under light-proof conditions; the certain reaction conditions are 90-110°C for 5-7 days. 2 The total amount of triethynylbenzene added to the copper foil is 100-200 mg.
[0040] d. The yellow-brown solid powder obtained in step c is subjected to a washing treatment under certain conditions, and finally calcined at a certain temperature under the protection of an inert atmosphere to obtain a hydrogen-substituted graphyne nanopowder material. Specifically, the washing treatment under certain conditions is washing treatment with an organic solvent, an acid solution and an alkaline solution in sequence, wherein the organic solvent is one or two of N,N-dimethylformamide (DMF) and acetone, centrifuged until the supernatant is colorless, the acid solution is 1M hydrochloric acid, and the alkaline solution is 1M NaOH solution; the calcination temperature is 200-400°C, and the calcination time is 2-6h.
[0041] The morphology of the hydrogen-substituted graphyne nanopowder material obtained by the invention is a stacked structure of spherical nanoparticles of about 10 to 300 nm.
[0042] Another aspect of the present invention also relates to the use of the above hydrogen-substituted graphyne nanopowder material as an adsorbent in the field of environmental remediation such as adsorption of heavy metals.
[0043] As a preferred solution, the hydrogen-substituted graphyne nanopowder material is used as an adsorbent for lead ions.
[0044] As another preferred embodiment, the hydrogen-substituted graphyne nanopowder material in the present invention is directly used as a heavy metal adsorbent for adsorbing lead in lead-containing water media without being modified by other physical and chemical methods.
[0045] In the hydrogen-substituted Graphyne nanopowder material of the present invention, no other materials are introduced as active sites, the process of preparing the adsorbent is reduced, the cost of the adsorbent is reduced, and the problem of low adsorption of lead ions by traditional Graphyne materials is solved. The hydrogen-substituted Graphyne nanomaterial prepared by the present invention has a powder structure, which increases the contact area between the material and the liquid medium, thereby improving the adsorption efficiency.
[0046] The present invention provides a hydrogen-substituted graphyne nanopowder material and a preparation method thereof and a new use thereof as a heavy metal adsorbent. In order to make the advantages and technical solutions of the present invention clearer and more specific, the present invention is described in detail below in conjunction with specific embodiments.
[0047] The raw materials required for the present invention can be purchased through commercial channels.
[0048] Embodiment 1:
[0049] Step a: 200 mg of 1,3,5-tris[(trimethylsilyl)ethynyl]benzene was dissolved in a solution of 60 mL of THF, and TBAF (1M in THF, 1.65 mL, 1.65 mmol) was added to the solution, and the mixture was stirred at 6°C for 30 minutes under light-shielding conditions. After the reaction, the solution was extracted with dichloromethane, washed with distilled water, dried over anhydrous sodium sulfate, filtered and the solvent was rotary evaporated to obtain 1,3,5-triethynylbenzene. 150 mg of 1,3,5-triethynylbenzene was dissolved in 100 mL of pyridine to form a 1.5 mg / ml solution.
[0050] Step b: Ultrasonicate copper foil (1 cm wide, 10 cm long, 0.1 cm thick, 20 pieces) in 1 M hydrochloric acid, water and acetone for 5 minutes respectively, dry in a nitrogen stream and immerse the copper foil in 80 ml of pyridine, and preheat at 100°C for 30 minutes to obtain mixture A.
[0051] Step c: The pyridine solution of triethynylbenzene was slowly added dropwise to the mixture A, and the reaction temperature was maintained at 100° C. for 5 days. The reaction solution was sonicated, and the solvent was evaporated.
[0052] Step d: The powder was centrifuged with N,N-dimethylformamide (DMF) and acetone until the supernatant was colorless to remove oligomers. Then refluxed with 20mL hydrochloric acid (HCl, 1M) at 80°C for 3 hours, filtered, and washed with pure water until the pH was neutral. Then refluxed with 20mL sodium hydroxide (NaOH, 1M) at 80°C for 3 hours, filtered, and washed with pure water until the pH was neutral. Then vacuum dried at 80°C for 24h, and finally the powder was heated at a rate of 5°C per minute in a tube furnace, and calcined at 300°C for 2 hours under a protective atmosphere to obtain a yellow-brown powder, which is a hydrogen-substituted Graphene nanopowder material.
[0053] The structure of the hydrogen-substituted graphyne nanopowder material synthesized by the present invention is as follows: Figure 1 As shown, from Figure 1 It can be seen that the material is composed of a phenyl unit with a conjugated large π bond and three diacetylenic units with acetylenic bonds.
[0054] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by SEM, and the results are as follows: Figure 2 As shown in the figure, it can be seen that the hydrogen-substituted graphyne nanopowder material is composed of stacked nanospheres of 50 to 80 nm.
[0055] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by HRTEM, and the results are as follows: Figure 3 As shown, the material presents a two-dimensional stacking with a certain interlayer spacing.
[0056] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by XRD, and the results are as follows: Figure 4 As shown in the figure, it can be seen that the hydrogen-substituted Graphyne nanopowder material has a characteristic diffraction peak representing a carbon material, proving the carbon skeleton structure of the hydrogen-substituted Graphyne nanopowder structure.
[0057] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by Raman, and the results are as follows: Figure 5 As shown, 1361cm -1 and 1577cm -1 The two characteristic peaks of wave number are attributed to the D band and G band of benzene ring, 2024cm -1 and 2197cm -1 The existence of the lower peak in wavenumber indicates that there are acetylenic bonds in the material, proving the integrity of the Graphdyne structure of the powder material.
[0058] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by XPS, and the C1s result was as follows: Figure 6 As shown, it represents sp hybridized carbon and sp 2 The peak area ratio of hybridized carbon is close to 1:1, which further confirms the structural characteristics of hydrogen-substituted graphyne.
[0059] The hydrogen-substituted graphyne nanopowder material obtained in this example was characterized by a nitrogen adsorption-desorption isotherm curve. Figure 7 It can be seen that the specific surface area (S BET ) is 160.5m 2 g -1 , further proving that the present invention has successfully prepared hydrogen-substituted graphyne nanopowder materials with a higher specific surface area.
[0060] Furthermore, the application effect of the prepared hydrogen-substituted graphyne nanopowder material in lead ion adsorption was investigated.
[0061] Application Example 1
[0062] 5 mg of hydrogen-substituted Graphene nanopowder material was added to a lead ion solution (200 mg / L, 30 mL) and stirred for 2 hours, and samples were taken at different time periods. Samples were taken with a syringe equipped with a microfiltration membrane, and the lead ion concentration in the solution was determined by ICP-AES.
[0063] The results are as follows Figure 8 As shown in the figure, when the adsorption equilibrium is reached after 30 minutes, the maximum adsorption amount of lead ions is 994 mg / g. The prepared hydrogen-substituted graphyne nanopowder material is in full contact with the liquid medium. The regulation of structure and morphology makes the material more hydrophilic, has better dispersibility in the solution, and has a larger specific surface area, thereby increasing the adsorption amount of lead ions.
[0064] Furthermore, 1 mg of hydrogen-substituted Graphene nanopowder material was used to adsorb lead ion solutions of different concentrations. The curve of the lead ion saturation adsorption amount of the material versus the equilibrium concentration of lead ions in the solution was as follows: Fig. 9 As shown in the figure, after fitting the Langmuir isotherm adsorption model, the maximum adsorption capacity of lead ions is 2390 mg· / g, which further confirms that the hydrogen-substituted graphyne nanopowder material has excellent lead ion adsorption performance.
[0065] Furthermore, in order to verify the cyclic stability of hydrogen-substituted Graphene nanopowder materials as adsorbents in practical applications, after acid extraction, the samples were washed with deionized water for neutralization and adsorption-desorption cycles were performed. In each cycle, 5 mg of adsorbent absorbed 10 mL of lead ion solution (200 mg / L). Fig.10 The results show that the adsorption amount of the material did not decrease significantly in 6 cycles and could be maintained at more than 90%. Therefore, it is proved that the hydrogen-substituted Graphene nanopowder material prepared by the present invention can be used as a reusable Pb 2+ Adsorbent.
[0066] Embodiment 2:
[0067] In step c, the pyridine solution of triethynylbenzene is slowly added dropwise to mixture A and reacted at 110° C. for 5 days. Other conditions are the same as those in Example 1. A hydrogen-substituted graphyne nanopowder material is prepared, and the morphology of the powder material is a stacked structure of spherical nanoparticles of about 50 to 300 nm.
[0068] Embodiment 3:
[0069] In step c, the pyridine solution of triethynylbenzene is slowly added dropwise to mixture A, and reacted at 90° C. for 5 days. Other conditions are the same as those in Example 1. A hydrogen-substituted graphyne nanopowder material is prepared. The morphology of the powder material is a structure in which a small amount of spherical nanoparticles of about 10 to 300 nm are stacked and gradually become flakes.
[0070] Embodiment 4:
[0071] In step a, 150 mg of 1,3,5-triethynylbenzene was dissolved in 150 mL of pyridine to form a 1.0 mg / ml solution. Other conditions were the same as those in Example 1 to prepare a hydrogen-substituted graphyne nanopowder material.
[0072] Embodiment 5:
[0073] In step a, 150 mg of 1,3,5-triethynylbenzene was dissolved in 50 mL of pyridine to form a 3.0 mg / ml solution. Other conditions were the same as those in Example 1 to prepare a hydrogen-substituted graphyne nanopowder material.
[0074] Comparative Example 1:
[0075] Step a: 200 mg of 1,3,5-tris[(trimethylsilyl)ethynyl]benzene was dissolved in a solution of 60 mL of THF, and TBAF (1M in THF, 1.65 mL, 1.65 mmol) was added to the solution, and the mixture was stirred at 6°C for 30 minutes under light-shielded conditions. After the reaction, the solution was extracted with dichloromethane, washed with distilled water, dried over anhydrous sodium sulfate, filtered and the solvent was rotary evaporated to obtain 1,3,5-triethynylbenzene. 150 mg of 1,3,5-triethynylbenzene was dissolved in 100 mL of pyridine to form a 1.5 mg / ml solution.
[0076] Step b: Ultrasonicate copper foil (1 cm wide, 10 cm long, 0.1 cm thick, 20 pieces) in 1 M hydrochloric acid, water and acetone for 5 minutes respectively, dry in a nitrogen stream and immerse the copper foil in 80 ml of pyridine, and preheat at 100°C for 30 minutes to obtain mixture A.
[0077] Step c: The pyridine solution of triethynylbenzene was slowly added dropwise to the mixture A, and the mixture was kept at 80° C. for 5 days. The reaction solution was ultrasonically treated, and the solvent was evaporated to obtain a film-like material.
[0078] Step d: The film material was centrifuged with N,N-dimethylformamide (DMF) and acetone until the supernatant was colorless to remove oligomers. Then refluxed with 20 mL of hydrochloric acid (HCl, 1M) at 80°C for 3 hours, filtered, and washed with pure water until the pH was neutral. Then refluxed with 20 mL of sodium hydroxide (NaOH, 1M) at 80°C for 3 hours, filtered, and washed with pure water until the pH was neutral. Then vacuum dried at 80°C for 24 hours, and finally the film material was heated at a rate of 5°C per minute in a tube furnace and calcined at 300°C for 2 hours.
[0079] The film material was finally characterized by SEM, and the results were as follows Fig.11 As shown, it can be seen from the figure that the material presents a film-like structure, indicating that a film-like hydrogen-substituted graphyne material is obtained at this reaction temperature. The hydrogen-substituted graphyne nanopowder material prepared in this application cannot be obtained.
[0080] Comparative Example 2:
[0081] In step c, the pyridine solution of triethynylbenzene is slowly added dropwise to mixture A, and reacted at 120° C. for 5 days. Other conditions are the same as those in comparative example 1. The hydrogen-substituted graphyne nanopowder material prepared in the present application cannot be obtained.
[0082] If the reaction temperature is too high, the pyridine solution will boil, and if the reaction temperature is too low, the powder material cannot uniformly form a nano-spherical stacking structure. Therefore, the present invention preferably reacts at 90-110°C.
[0083] Comparative Example 3:
[0084] In step a, 150 mg of 1,3,5-triethynylbenzene was dissolved in 150 mL of pyridine to form a 0.5 mg / ml solution. In step c, the pyridine solution of triethynylbenzene was slowly added dropwise to mixture A and reacted at 110° C. for 5 days. Other conditions were the same as those in comparative example 1. The hydrogen-substituted graphyne nanopowder material prepared in the present application could not be obtained.
[0085] Comparative Example 4:
[0086] In step a, 150 mg of 1,3,5-triethynylbenzene was dissolved in 150 mL of pyridine to form a 4 mg / ml solution. In step c, the pyridine solution of triethynylbenzene was slowly added dropwise to mixture A and reacted at 110° C. for 5 days. Other conditions were the same as those in comparative example 1. The hydrogen-substituted graphyne nanopowder material prepared in the present application could not be obtained.
[0087] Too high a monomer concentration will cause serious agglomeration of the powder material, and too high a monomer concentration will reduce the yield of the powder material. Therefore, the present invention preferably reacts in a solution of 1.0 to 3 mg / ml formed by dissolving 1,3,5-triethynylbenzene in pyridine.
[0088] The preparation method of the present invention comprises the following steps: (1) using 1,3,5-tris[(trimethylsilyl)ethynyl]benzene as a raw material, obtaining triethynylbenzene through desiliconization reaction, and obtaining a pyridine solution of triethynylbenzene; (2) adding copper foil and pyridine to a reaction container under a protective atmosphere, and then adding the pyridine solution of triethynylbenzene, and polymerizing to obtain a brown-yellow solid powder; (3) the obtained brown-yellow solid powder is treated with acid, alkali and high temperature to obtain a hydrogen-substituted graphyne nanopowder material, and the material is directly used for removing lead ions in an aqueous medium without other treatment. The preparation method of the present invention requires simple equipment and is easy to operate. The hydrogen-substituted graphyne nanopowder material prepared by the present invention has the characteristics of good dispersibility in aqueous media, an electron-rich diacetylene bond structure, a hexagonal pore structure composed of 42 carbon atoms and a spherical nanoparticle morphology, which are all conducive to its full contact with and capture of lead ions in a liquid medium, and the special pore structure can improve the diffusion of ions and thus improve the adsorption of heavy metals. When the material of the present invention is used as a heavy metal adsorbent to remove lead ions in water medium, the maximum adsorption capacity of lead ions is 2390 mg·g -1 Compared with the reported materials, the hydrogen-substituted graphyne nanopowder material exhibits the largest lead ion adsorption capacity. The present invention prepares the hydrogen-substituted graphyne nanopowder material for the first time and applies it to the adsorption of heavy metal lead ions, providing a new opportunity for the development of new heavy metal adsorbents.
[0089] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a hydrogen-substituted graphyne nanopowder material, characterized in that: The following steps are involved: The triethynylbenzene solution is added to the mixture A containing the copper foil, and reacted at 90-110° C. to generate solid powder, and the solid powder is washed and calcined to obtain a hydrogen-substituted graphyne nanopowder material; The concentration of triethynylbenzene solution is 1 to 3 mg / mL; The reaction is carried out under light-proof conditions and the reaction time is 5 to 7 days.
2. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 1, characterized in that: The solvent of the triethynylbenzene solution is pyridine.
3. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 1, characterized in that: The preparation of triethynylbenzene comprises the following steps: A tetrabutylammonium fluoride solution is added to a 1,3,5-tri[(trimethylsilyl)ethynyl]benzene solution, wherein the ratio between 1,3,5-tri[(trimethylsilyl)ethynyl]benzene and tetrabutylammonium fluoride is 200 mg: (1.5-1.8) mmol; the mixture is stirred at 2-10° C. for 15-45 min under light-proof conditions, and then post-treated to obtain triethynylbenzene.
4. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 3, characterized in that: The solvents of the 1,3,5-tris[(trimethylsilyl)ethynyl]benzene solution and the tetrabutylammonium fluoride solution are both tetrahydrofuran; and the post-treatment comprises dichloromethane extraction, water washing, drying, filtering and evaporating the solvent.
5. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 1, characterized in that: The mixture A containing copper foil is obtained by placing copper foil in pyridine and preheating at 80 to 100° C. for 20 to 40 minutes.
6. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 1, characterized in that: Washing is carried out by washing with an organic solvent, an acid solution and an alkali solution.
7. The method for preparing hydrogen-substituted graphyne nanopowder material according to claim 1, characterized in that: The calcination is carried out at 200-400°C for 2-6 hours.
8. The hydrogen-substituted graphyne nanopowder material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the hydrogen-substituted graphyne nanopowder material as claimed in claim 8 in adsorbing heavy metals.
Citation Information
Patent Citations
Preparation method of biological carbon for removing heavy metal lead from water body
CN107362772A
Preparation method of heavy metal ion adsorbent
CN108993446A
Preparation method and application of lead adsorption magnetic graphene oxide composite material
CN111013535A